Social Conflict as a Perspective in Interdisciplinary Islamic Studies - Mutamakin Mutamakin (UIN Sjech M. Djamil Djambek Bukittinggi, 2023)
Interdisciplinary studies demand an understanding of multiple disciplines across disciplines. In the social sciences discipline, the results of sociology research are growing rapidly and have formulated new theories that can be utilized in interdisciplinary studies. Among these is the theory of social conflict. The perspective of social conflict departs from the assumption that inequality exists in all societies. Social conflict theory focuses on various aspects of power status in social positions. Individual identification characteristics are viewed from ethnic or ethnic perspectives, gender, age, religion, expertise, and social status. This social conflict theory can be applied as a perspective in interdisciplinary Islamic studies, this is due to the aim of Islamic studies is to describe the relationship between Islam and various aspects of human life, explaining the spirit (ethos) of Islam in the form of moral and values within Islamic teaching. Thus, approaching Islam through the lens of social conflict theory within Islamic studies got it relevance as Islamic teaching responses to various new paradigms as a result of advances in science and technology and the emergence of new philosophies and ideologies as well as the relationship between Islam and the vision, mission, and goals of Islamic teachings.